IMPLEMENTASI SISTEM PENJAMINAN MUTU INTERNAL (SPMI) DALAM MEWUJUDKAN GOOD UNIVERSITY GOVERNANCE (GUG) - Samsul Rizal; Moh Aris Pasigai; M.Yusuf Alfian Rendra Anggoro; Ramlah; Wahyuddin (UHN IGB Sugriwa Denpasar, 2023)
The aims of this study are to: 1) describe the implementation of the Internal Quality Assurance System (SPMI) in realizing Good University Governance (GUG), and 2) describe the influence of SPMI on GUG. This research was a mixed method with the design used explanatory research design. The population of this research were the lecturers of the Faculty of Economics and Business with 75 persons where the key informants namely lecturer representatives, and heads of study programs/faculty. Collecting data through questionnaires and interviews which were then processed by simple regression analysis and qualitative data obtained by reduction, data presentation, and drawing conclusions. The results of the research study concluded that; 1) The implementation of SPMI in realizing GUG is carried out in the following the applicable standards included the evaluation which carried out in the form of an internal quality audit to determine the fulfillment of the National Higher Education Standards 2) The coefficient of influence of the application of SPMI on GUG is 0.539 with p value = 0.000 <0.05. This shows that SPMI has a significant positive influence on GuG with 56.3%. This can be stated that the better the implementation of SPMI, the realization of GUG in the Faculty of Economics and Business is better.